Tren dan Research Gap Life Cycle Cost Analysis pada Teknologi Energi Terbarukan: Systematic Literature Review - Andika Dwi Putra (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
This study aims to identify research trends and research gaps in the application of Life Cycle Cost Analysis (LCCA) in renewable energy technologies. A Systematic Literature Review (SLR) approach was employed using the PRISMA framework. The literature was collected from Scopus, ScienceDirect, IEEE Xplore, and Google Scholar databases with a publication range of 2015–2025. Approximately 350 articles were identified and filtered through several stages, resulting in 30–40 final articles for analysis. The findings indicate that solar photovoltaic systems dominate LCCA studies, followed by wind, biomass, and hybrid systems. Bibliometric analysis using VOSviewer reveals three main clusters: sustainability and literature review, management and sustainable development, and technical energy systems such as biomass and hydrogen. The results also show a shift in recent studies toward digitalization, artificial intelligence, and digital twin integration. However, inconsistencies in methodological approaches and limited studies in developing countries remain significant research gaps. This study provides a structured overview of LCCA development and identifies future research directions.